Pengaruh Media Pembelajaran Kartu Papan Pintar Literasi Terhadap Kemampuan Membaca Permulaan Siswa Kelas II SD Negeri Balfai - Saputri Marsa, Angelina; E. Noya Nahak, Kristina; Bernard Mbuik, Heryon (UNIB Press, 2025)
This study aims to analyze the effect of using the Smart Literacy Board Card learning media on the early reading skills of second-grade students at SD Negeri Balfai. This research employs a quantitative approach with a pre-experimental design, specifically a one-group pre-test post-test design. The study involved 21 students, with data collected through oral tests and observations. The results indicate a significant improvement in students' early reading skills after the implementation of this learning media. The Paired Sample t-test results showed a value of p = 0.000 < 0.05, indicating a significant difference between the pre-test and post-test scores. The use of the Smart Literacy Board Card has proven effective in helping students recognize letters, syllables, and sentences more effectively while also increasing their motivation to learn. These findings suggest that utilizing interactive and innovative learning media can enhance the quality of early reading instruction at the elementary school level.